Influence of BPA exposure, measured in saliva, on childhood weight - Heras-González, Leticia; Espino, Diana; Jimenez-Casquet, Maria Jose; Lopez-Moro, Alejandro; Olea-Serrano, Fatima; Mariscal-Arcas, Miguel (Frontiers in Endocrinology, 2022)
Endocrine disruptors such as bisphenol A (BPA), BPA glycidyl methacrylate, and other BPA acrylate-based derivatives have been related to type 2 diabetes, the metabolic syndrome, and obesity, among other metabolic disorders. The objective of this study was to examine the influence of BPA exposure by saliva analysis and daily physical activity on the risk of overweight/obesity in schoolchildren from southern Spain. The study included 300 children (53.5 % female) aged 7-10 years. Participants completed a questionnaire with four sections: participant data, including demographic information and life and family habits; semi-quantitative food frequency questionnaire; anthropometric variables, and physical activity variables. All participants underwent dental examination, when the presence of sealants/composites in each tooth and other dental alterations were recorded, and samples of whole saliva were collected for UHPLC–MS/MS analyses. Risk of overweight/obesity was significantly influenced by body fat composition (OR= 10.77), not walking to and from school (OR= 1.38), lesser energy expenditure in sedentary activities (OR= 12.71), greater energy expenditure in sports (OR=1.62), and exposure to BPA from dental sealants/composites (OR= 1.38; p= 0.058). Further research is warranted on this issue in children, who may be especially vulnerable to the negative health effects of endocrine disruption.